2009
DOI: 10.1017/s003060530999041x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid degradation of a Mauritian rainforest following 60 years of plant invasion

Abstract: Rapid degradation of a Mauritian rainforest following 60 years of plant invasion M a l i k a V i r a h-S a w m y , J o h n M a u r e m o o t o o , D o r e e n M a r i e , S a o u d M o t a l a and J e a n-C l a u d e S e v a t h i a n

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 29 publications
2
10
0
Order By: Relevance
“…This lends further support to the suggestion of creating new conservation areas elsewhere than in the southwest of the island. The forests studied have all been impacted by human activities, whether directly, like native palm heart extraction (Cheke and Hume 2008), or through the impact of introduced invasive animals (for example, fruit predators like long tailed macaques (Baider and Florens 2006) and plants (Florens 2008, Virah-Sawmy et al 2009Baider and Florens 2011). For example, palms, which used to be abundant in wet forests in the 1760s (Bernardin de Saint Pierre 1773) are completely absent from the sample plots.…”
Section: Beta Diversity and Conservationmentioning
confidence: 98%
See 1 more Smart Citation
“…This lends further support to the suggestion of creating new conservation areas elsewhere than in the southwest of the island. The forests studied have all been impacted by human activities, whether directly, like native palm heart extraction (Cheke and Hume 2008), or through the impact of introduced invasive animals (for example, fruit predators like long tailed macaques (Baider and Florens 2006) and plants (Florens 2008, Virah-Sawmy et al 2009Baider and Florens 2011). For example, palms, which used to be abundant in wet forests in the 1760s (Bernardin de Saint Pierre 1773) are completely absent from the sample plots.…”
Section: Beta Diversity and Conservationmentioning
confidence: 98%
“…Sussman (1986, 1988) later described the wet native forest community at two other sites where they also conducted the first study of the extent of alien plant invasion. More recently, Virah-Sawmy et al (2009) compared the surveys of Vaughan and Wiehe (1941) with more recent sampling and implied that invasive alien plants could be a major driver of tree species richness and density decline. However, the results of this study were somewhat limited because it could not be carried out at the exact locations of the plots of Vaughan and Wiehe (1941) since nine of the ten plots surveyed could not be relocated.…”
Section: Introductionmentioning
confidence: 98%
“…When exotic tree species do spread beyond their point of introduction, however, they have the potential to be more damaging than smaller plants [1]. They create shade, which is a barrier to the reestablishment of many native species [4,5]; they can dominate nutrient cycling, potentially changing the site in a more permanent way [6,7,8]; and they can make the invaded habitat less suitable for arthropods [9] and native vertebrates [10]. Other reported impacts of some tree invasions include allelopathic suppression of competitors [11,12], changes in the local fire regime [13], and reduced streamflow [14].…”
Section: Introductionmentioning
confidence: 99%
“…This seems particularly relevant when considering the conservation of Mauritian understory plants, because studies on vegetation changes in the Mauritian lowland wet forests reported a greater decline for these plants compared to canopy species [19][20]. For example a survey of a plot in a lowland forest in 1986, which was initially sampled in the late 1930s when few IAP were present, found that the lowermost native plant strata of the forest had almost entirely disappeared, with a higher mortality rate for the shorter species compared to larger tree species [19].…”
Section: Implications For Conservationmentioning
confidence: 99%
“…Species richness and density of native seedlings and adult woody plants as well as native butterflies are greater in areas where IAP are controlled [14,[16][17]. It also appears that over the last century or two, several Mauritian shade tolerant, understory native plants have declined more severely than taller species [18][19][20][21]. This Tropical Conservation Science | ISSN 1940-0829 | Tropicalconservationscience.org 37 supports findings that understory and herbaceous ground flora are among the species that recovered best when IAP are controlled [17], suggesting that alien plants may play a pivotal role in driving the long term decline of understory species.…”
Section: Introductionmentioning
confidence: 99%